Feasibility and scope of teledentistry services during the COVID-19 pandemic – A cross-sectional study - Swati Jain; Vikrant Mohanty (Journal of Indian Association of Public Health Dentistry, 2023)
Introduction: COVID-19 pandemic has influenced health-care utilization globally accentuating oral disease burden. This has reinforced the role of telemedicine. However, being technologically sensitive; the concept is still not popular. Hence, the present study aims to assess the scope and feasibility of teledentistry services of a Mobile Dental Clinics. Methodology: Teledentistry services were provided to the old patients of Mobile Dental Clinic Project for follow-up care from May 2021 to June 2021. Contact details of the patients were retrieved and were contacted for teleconsultation services using smartphones. Data were recorded through a prestructured digital outpatient department and feedback form. Results: A total of 813 active calls were made to provide teledentistry services. The response rate was 26.33% (n = 214). Around 78.5% (n = 168) of the study respondents did not have any current chief complaint related to oral health. Those who suffered from some ailment (11.2%) complained majorly of “dental pain.” Around 34.6% (n = 74) still required further dental treatment. The majority (97.7%) were satisfied with the teledentistry services provided. Discussion: Mostly, the patients could not be contacted due to COVID-19-related lockdown and migration from the city. From the patients who were followed up, 21.5% reported having some dental complaint. This clearly showed that these patients had received dental treatment even during pandemic. Furthermore, the felt need in the community was quite high leading to health-seeking behavior previously. Conclusion: In the view of COVID-19 preventive measures, it is advocated that teledentistry services should be implemented to improve oral healthcare outreach.